PENGARUH LUAS LAHAN TERHADAP PENDAPATAN PETANI KARET DI DESA PULAU INGU KPECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Gustina, Desi Gustina Desi; Selva Johan, Rina Selva Johan Rina; Armas, Riadi Armas Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This Result aims to determine the effect on the performance of the farm to earnings of farmer of rubbers Country side of Island of Ingu of Sub district of Benai of Regency of Pestle Singingi. This Research in Country side of Island of Ingu from August 2014 till finish. Method of Research used quantitative descriptive method. Population is all farmer of rubber Country side of Island of Ingu as much 60 responder which is selecting as a sample. Data collection instrument used was a questionnaire and data analysis with model of simple linear regression. Result of this research indicate that wide farm have an effect on signifikan to earnings of farmer of rubbers Countryside of Island of Ingu of Subdistrict of Benai of Regency of Pestle Singingi. This Matter seen from result test simple linear regression with level of signifikan 5% obtained a f value to wide of farm < 1 Ha F-hitung > F-tabel ( F-Hitung 1894.013 > F-Tabel 4,10) evidence indicating that F-hitung > Wide F-tabel farm have an effect on to earnings of farmer of rubber equal to 98,0%, to wide of farm 1-2 Ha Fhitung > Ftabel ( F-Hitung 141.963 > F-Tabel 4,75) wide variable farm to earnings equal to 93,4%, to wide farm > 2 Ha F-hitung > F-tabel ( F-Hitung 442.300 > F-Tabel 5,99) influence of wide variable farm to earnings equal to 98,4 Key words : Wide Farm, Earnings